Interaction of copper potential metallodrugs with TMPRSS2: A comparative study of docking tools and its implications on COVID-19 - Vazquez-Rodriguez, Sergio; Ramírez-Contreras, Diego; Noriega, Lisset; García-García, Amalia; Sánchez-Gaytán, Brenda L.; Melendez, Francisco J.; Castro, María Eugenia; de Azevedo, Walter Filgueira; González-Vergara, Enrique (Frontiers in Chemistry, 2023)
SARS-CoV-2 is the virus responsible for the COVID-19 pandemic. For the virus to enter the host cell, its spike (S) protein binds to the ACE2 receptor, and the transmembrane protease serine 2 (TMPRSS2) cleaves the binding for the fusion. As part of the research on COVID-19 treatments, several Casiopeina-analogs presented here were looked at as TMPRSS2 inhibitors. Using the DFT and conceptual-DFT methods, it was found that the global reactivity indices of the optimized molecular structures of the inhibitors could be used to predict their pharmacological activity. In addition, molecular docking programs (AutoDock4, Molegro Virtual Docker, and GOLD) were used to find the best potential inhibitors by looking at how they interact with key amino acid residues (His296, Asp 345, and Ser441) in the catalytic triad. The results show that in many cases, at least one of the amino acids in the triad is involved in the interaction. In the best cases, Asp435 interacts with the terminal nitrogen atoms of the side chains in a similar way to inhibitors such as nafamostat, camostat, and gabexate. Since the copper compounds localize just above the catalytic triad, they could stop substrates from getting into it. The binding energies are in the range of other synthetic drugs already on the market. Because serine protease could be an excellent target to stop the virus from getting inside the cell, the analyzed complexes are an excellent place to start looking for new drugs to treat COVID-19.